The Role of Artificial Intelligence In Understanding And Answering Investors' Questions In Arabic - Rusul Albahrani; Nagham Neama; Akram Afsay (Indonesian Journal Publisher, 2026)
This research aims to study the role of artificial intelligence (AI) in accurately understanding and answering investors' questions written in Arabic, thereby supporting investment decision-making and improving communication between investors and digital financial systems. This article explores the potential of AI in providing financial guidance. The study's significance lies in the increasing importance of AI technologies in financial markets, particularly given the rapid growth of digital financial services and investors' growing reliance on electronic platforms for financial information. Twenty questions from the Basic Financial Literacy Questionnaire and the Big Five factors were used to evaluate the ChatGPT-3.5 and ChatGPT-4 models. The study adopted a descriptive-analytical approach to examine the role of AI technologies in understanding investment issues, in addition to employing a range of statistical methods to analyze data and test relationships between study variables. Furthermore, combining financial literacy and AI, while considering ethical awareness, leads to the optimal use of AI-assisted financial advice. This strategy contributes to mitigating the risks of over-reliance on AI, fostering informed trust in AI systems, and enabling better financial decision-making. The study results showed that using artificial intelligence technologies, particularly natural language processing models, significantly improves the understanding of investment questions in Arabic and increases the accuracy of the answers provided to investors. It also reduces the time required to obtain financial information. Furthermore, the results indicated that adopting intelligent systems in investment platforms can enhance investor confidence, increase transparency, and facilitate more efficient investment decisions. Based on these findings, the study recommends developing specialized AI applications in the financial sector in Arabic and expanding their use in financial institutions and investment platforms.